Encyclopedia of Biostatistics 2005
DOI: 10.1002/0470011815.b2a10015
|View full text |Cite
|
Sign up to set email alerts
|

Contagious Distributions

Abstract: Polya proposed a model for the spread of an infection, whereby the probability of catching a disease depended on the existing number of cases. This leads to a distribution that has a limiting negative binomial form. Neyman proposed an alternative approach that arises from a Poisson distribution of clumps, with the number of cells for each clump being Poisson. This article surveys probability distributions and corresponding generating functions that result from such constructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…55 A striking feature is their predominance in Zone 1 where 57 % of them occur versus 10 to 22 % in the other zones. 56 An analysis of the orientation of plots according to the cardinal points has suggested that fields in Zone 1 principally follow the Bahr Yussef, while another part lies on the left bank of the Nile. 57 In Zone 2 fields mostly adjoin the riverbank and in Zone 3 they are generally at a distance from watercourses, probably being located in the central part of the floodplain.…”
Section: The Irrigation System In the Land Registersmentioning
confidence: 99%
See 4 more Smart Citations
“…55 A striking feature is their predominance in Zone 1 where 57 % of them occur versus 10 to 22 % in the other zones. 56 An analysis of the orientation of plots according to the cardinal points has suggested that fields in Zone 1 principally follow the Bahr Yussef, while another part lies on the left bank of the Nile. 57 In Zone 2 fields mostly adjoin the riverbank and in Zone 3 they are generally at a distance from watercourses, probably being located in the central part of the floodplain.…”
Section: The Irrigation System In the Land Registersmentioning
confidence: 99%
“…Sebakh extraction had no doubt happened earlier, but not previously on such a scale. 56 In some ways, the humbler manifestations of human cultures -broken and salty sherds, ashy deposits, windblown sand lenses, ancient earthworks -are denied legitimacy and a place in a culture's and a discipline's narrative when they are demoted to such a binary state: "antiquities" vs. "sebakh;" "archaeological land" vs. "lands declared free of monuments or artefacts. "…”
Section: Writing a Future Companionmentioning
confidence: 99%
See 3 more Smart Citations